RETRACTED: Assessment of the productivity of river sediments - Arifjanov Aybek; Samiyev Luqmon; Babajanov Farrukh; Tadjiboyev Suhrob; Akramov Jamoliddin (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001